MAWAS DIRI: DINAMIKA KESEJAHTERAAN PSIKOLOGIS PENGASUH ORANG DENGAN GANGGUAN JIWA DALAM PERSPEKTIF KAWRUH JIWA - Assyafii, Husain Ali; Primadasa, Arizal; Dewi, Innayah Kusuma; Prihartanti, Nanik (Program Studi S1 Psikologi, 2024)
The family is the primary caregiver that is needed by people with mental disorders (ODGJ). Caring for ODGJ can be a challenge to the psychological well-being of the family as caregivers. This research aims to understand the dynamics of psychological well-being in families as caregivers of ODGJ from the perspective of mental health. The research method used is descriptive qualitative. Research subjects were taken using purposive sampling, and six family members of ODGJ were selected with the criteria: (1) being a family member as a caregiver for ODGJ for a minimum of five years and (2) being of Javanese ethnicity. Data collection uses semi-structured interviews. Data analysis was done by reducing interview data and interpreting it based on the kawruh jiwa perspective. The results of the research show that there are dynamics of psychological well-being through efforts to rationalize notes or introspection carried out by subjects on three themes: (1) social themes, (2) economic themes, and (3) spiritual themes. It is crucial to conduct research with an indigenous perspective to review the dynamics of psychological well-being in the sociocultural context.